The role of epidermal sphingolipids in dermatologic diseases - Borodzicz, Sonia (Lipids Health Dis, 2016)
Sphingolipids, a group of lipids containing the sphingoid base, have both structural and biological functions in human epidermis. Ceramides, as a part of extracellular lipids in the stratum corneum, are important elements of the skin barrier and are involved in the prevention of transepidermal water loss. In addition, ceramides regulate such processes as proliferation, differentiation and apoptosis of keratinocytes. Another important sphingolipid, sphingosine-1-phosphate (S1P), inhibits proliferation and induces differentiation of keratinocytes. A recent clinical study of the efficacy and safety of ponesimod (a selective modulator of the S1P receptor 1) suggested that sphingolipid metabolism may become a new target for the pharmacological treatment of psoriasis. The role of sphingolipids in some dermatologic diseases, including psoriasis, atopic dermatitis and ichthyoses was summarized in this article.